THE INFLUENCE OF APPRENTICESHIP AND WORK MOTIVATION ON THE WORK READINESS OF CLASS XII WELDING ENGINEERING STUDENTS AT SMKN 10 MALANG - Dian Putri Noorhasanah; Marsono; Puteri Ardista Nursisda Mawangi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Preliminary observations at SMKN 10 Malang revealed that 40% of students who had completed an industrial work practice still exhibited a lack of readiness to enter employment. This study aims to examine the effect of apprenticeship (industrial work practice) and work motivation on the work readiness of twelfth-grade Welding Engineering students at SMKN 10 Malang, both partially and simultaneously. The research employed an ex post facto design with a quantitative approach. The population comprised 45 students, all of whom were taken as the sample using a saturated sampling technique. The instrument was a four-point Likert scale questionnaire that has been tested for validity and reliability. The data were analyzed using multiple linear regression with the aid of SPSS. The results showed that, partially, apprenticeship experience did not have a significant effect on work readiness (t = -1.284; Sig. = 0.206), whereas work motivation had a positive and significant effect (t = 10.524; Sig. < 0.001). Simultaneously, both variables significantly affected work readiness (F = 94.286; Sig. < 0.001) with a coefficient of determination (R Square) of 0.809, indicating that 80.9 % of the variance in work readiness was explained by these two variables. These findings confirm that work motivation is the primary predictor of students' work readiness, while apprenticeship experience in the context of this study did not make a significant partial contribution. The implication is that strengthening work motivation should be prioritized in efforts to enhance the work readiness of welding engineering students.